Flexibly modeling age trends in the prevalence of co-occurring patterns of substance use and mental health disorders using time-varying effects and latent class analysis. (4th May 2022) - Stull, Samuel W.; Linden-Carmichael, Ashley N.; Cloutier, Renee M.; Bonny, Andrea E.; Lanza, Stephanie T.
ABSTRACT: Background: Substance use disorders (SUDs) and mental health disorders may change and co-occur in complex patterns across adult ages, but these processes can be difficult to capture with traditional statistical approaches. Objective: To elucidate disorder prevalence and comorbidities across adult ages by using time-varying effect models (TVEMs), latent class analysis (LCA), and modeling latent class prevalences as complex functions of age. Methods: Data were drawn from participants who are 18–65 years old in the National Epidemiologic Survey on Alcohol and Related Conditions III (n = 30, 999; 51% women) and a subsample who reported a past-year post-traumatic stress disorder (PTSD), mood, anxiety, or SUD based on DSM-5 diagnoses (n = 11, 279). TVEM and LCA were used to examine age trends and comorbidity patterns across ages. Results: SUD prevalence peaked at age 23 (31%) and decreased thereafter, while mental health disorder prevalence was stable (20%–26% across all ages). The prevalence of five classes of individuals based on specific combinations of mental health and SUDs varied by age: the Alcohol Use Disorder class had the highest prevalence at age 26, whereas the Mood and Anxiety Disorder classes peaked around age 63. Interestingly, the Poly-Disorder class prevalence was greatest at age 18 but decreased sharply across young adulthood; however, the prevalence of the other high comorbidity class, PTSD with Mood or Anxiety Disorder, remained fairly constant across age, peaking at age 44. Conclusions: Multimorbid mental health disorders (excluding SUDs) persist in prevalence across adult ages. LCA, TVEM, and their integration together hold substantial potential to advance addiction research.